(untitled) (The Research of Medical Science Review, 2025)
Background: Ductal carcinoma in situ (DCIS) is the most common form of non-invasive breast cancer, and its early detection is vital for improving outcomes, especially in high-risk populations. This study evaluates the effectiveness of breast magnetic resonance imaging (MRI) in identifying DCIS, focusing on its diagnostic accuracy compared to histopathology, the gold standard. Objective: To Evaluate the breast Magnetic Resonance Imaging (MRI) in detecting Ductal Carcinoma In Situ (DCIS) lesions among high-risk breast cancer patients while keeping the histopathology as a GOLD standard. Results: This prospective observational study at INMOL Lahore involved 40 high-risk breast cancer patients aged 30-60, assessing breast MRI's diagnostic performance through demographic, clinical, and histopathological analysis. Descriptive statistics and cross-tabulation were used for evaluation.The results showed that 75% of participants had positive MRI findings for DCIS, with histopathology confirming DCIS in 70% of cases. MRI demonstrated a sensitivity of 90% and a specificity of 70%. Non-mass-like enhancement was the most common imaging feature, seen in 60% of cases, followed by nodular enhancement in 25%. Most participants were classified as BI-RAD 6 (67.5%), indicating known malignancy. Risk factors included a family history of breast cancer (25%) and prior cancer diagnoses (58%). Conclusion: These findings highlight MRI's high sensitivity in detecting DCIS, making it a valuable tool for early diagnosis in high-risk individuals, particularly those with dense breast tissue or genetic risk factors. However, the moderate specificity emphasizes the need for histopathological confirmation to minimize false-positive results. This study underscores the importance of integrating breast MRI into screening programs for high- risk populations. Further research with larger sample sizes and broader institutional involvement is necessary to improve imaging protocols and enhance diagnostic precision.